The potential of means of academic singing in shaping the aesthetic taste of future music teachers - Wanyi, Lin; Vasilyeva, Oksana (Professional Art Education, 2024)
Object. The purpose of this article is to examine the influence of means of academic singing on shaping aesthetic taste among future music teachers. Methods & methodology. Analysis of domestic and foreign scientific literature to generalize and systematize essential aspects of cultivating aesthetic taste in future music teachers; comparison method to study the peculiarities of Chinese and Ukrainian vocal traditions; systematization of information for the classification of means of academic singing. Results. The article explores the potential of means of academic singing in cultivating the aesthetic taste of future music teachers. The author analyzes the role of academic vocal methods as a powerful tool for shaping aesthetic taste among students in pedagogical fields within the scientific perspectives of Ukraine and China. The impact of academic singing on the development of aesthetic perception and critical thinking during the educational process is assessed. Various vocal techniques and their influence on the ability of future teachers to interpret musical works, which is a key aspect of professional training, are examined. The author emphasizes the importance of integrating vocal practices into the overall music education system to enhance the level of artistic and aesthetic education. The following means of academic singing have been characterized and classified: various genres of vocal works composed by composers from different historical periods and styles, including vocal pieces from ancient medieval music, the Renaissance, Baroque, Classicism, Romanticism, Neoclassicism, Postmodernism, and others; educational and methodological literature, such as collections of vocal exercises for developing vocal skills, anthologies of musical scores, repertoire collections, instructional manuals on voice training, and monographs on the history of vocal art; vocal events, including lectures on the theory and history of vocal art, vocal-literary evenings, thematic, anthology, and solo concerts, and vocal shows; vocal mastery techniques, such as skills in sound production, means of voice formation, sound extraction, breathing, and vocal support; and vocal musical expressiveness, including melody, rhythm, harmony, tonality, dynamics, and diction. Conclusions. Aesthetic taste is a complex and multifaceted phenomenon that reflects an individual’s ability to recognize and appreciate beauty in its various manifestations. It plays a significant role in cultural and social life, helping to shape both individual and collective perceptions of what is beautiful. Vocal art, as a means of perceiving and expressing musical ideas and emotions, plays a crucial role in the formation and development of aesthetic taste, thanks to the diverse techniques of academic singing.